Hydrogen-natural gas combustion in a marine lean-burn SI engine: A comparitive analysis of Seiliger and double Wiebe function-based zero–dimensional modelling. (1st March 2020) - Sapra, Harsh; Godjevac, Milinko; De Vos, Peter; Van Sluijs, Wim; Linden, Youri; Visser, Klaas
Abstract: With increasingly stringent emission regulations, marine natural gas engines need to improve their performance. Various proven advantages of hydrogen-natural gas (H-NG) blends make them a promising enhanced fuel solution. Although modelling of H-NG combustion has been investigated before, mostly using CFD models, the literature on the modelling capabilities of Seiliger-based and Wiebe-based zero-dimensional (0-D) models is limited for H-NG combustion. Especially for the application of marine lean-burn spark-ignited (SI) engines. Therefore, the aim of this paper is to compare the capabilities of Seiliger-based and double Wiebe function-based 0-D models to capture H-NG combustion in a marine SI engine for different H-NG fuel blends, engine leaning (lean-burn operation) and engine loads. In this work, measurements on a turbocharged, SI marine natural gas engine were used to develop a heat release rate model, which was subsequently used as a basis for the Seiliger and double Wiebe function-based H-NG combustion characterization models. Results from the two combustion modelling approaches were compared for different H-NG fuel blends, engine leaning (lean-burn operation) and engine loads. The modelling results were also compared against engine measurements for different experimental conditions. This paper shows that the Seiliger modelling approach can be used to define different physical phenomenon in H-NG combustion, while accurately capturing the effects of hydrogen addition and engine leaning on the H-NG combustion process at varying engine loads. This research also found that the variations in late burn phase present in lean-burn NG and H-NG combustion can be captured using the double-Wiebe modelling approach, however, clear trends of the Wiebe combustion parameters for varying fuel blends and engine loads could not be identified to accurately capture the H-NG combustion process. Furthermore, Wiebe-based modelling approach produced larger errors in the estimations of work output and combustion heat for all test conditions.